2018
DOI: 10.1007/s11136-018-2071-5
|View full text |Cite
|
Sign up to set email alerts
|

A note on the relationship between age and health-related quality of life assessment

Abstract: Purpose To extend existing analyses of whether and how the age of respondents is related to their time trade-off (TTO) valuations of hypothetical EQ-5D-3L health states, and to contribute to the existing debate about the rationale and implications for using age-specific utilities in health technology assessment (HTA). Methods We use data from the MVH UK valuation study. For each profile, the mean TTO value—adjusted by sex, education, self-reported health and personal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…This in turn suggests that the use of patient values in economic evaluations may lead to socio-demographic and/or health status inequalities. To illustrate, in line with previous research [44], older patients were found to systematically rate their own health lower than younger patients. As a consequence, the incremental gain from restoring older people to full health will likely be greater than that of younger people.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This in turn suggests that the use of patient values in economic evaluations may lead to socio-demographic and/or health status inequalities. To illustrate, in line with previous research [44], older patients were found to systematically rate their own health lower than younger patients. As a consequence, the incremental gain from restoring older people to full health will likely be greater than that of younger people.…”
Section: Discussionsupporting
confidence: 84%
“…In line with findings of Cubi-Molla et al (2019), this also suggests that older people value their own health state lower than younger people do. Please note that this is true because general public values are fixed, meaning that every EQ-5D-3L health state is only associated with one utility value, whereas patient values are variable and may thus in- or decrease with age [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the EQ-5D-Y-3L instrument is recommended to be used on a population in the age range of 8-15 years, it seemed appropriate to keep with our selected framing of a 10-year-old child for developing a unique country-specific EQ-5D-Y-3L value set. It should be noted that the EuroQol Group does not normally generate age-specific value sets for different adult age subgroups (or indeed any other subgroups) [35,36]. However, as preferences regarding the health of 10-year-old children may differ from preferences regarding the health of children or adolescents of other ages, further research is needed on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors see this as problematic, 34 because this aggregation is insufficiently sensitive to preference heterogeneity, and age is a demonstrable source of heterogeneity in valuation of the EQ-5D. 35 Extending the individual perspective to the valuation of the EQ-5D-Y would imply that only adults' age-specific preferences are considered, while excluding age-specific preferences for and of children and adolescents themselves.…”
Section: Why May An Individual Perspective For Valuation Of Eq-5d-y Health States Be Inappropriate?mentioning
confidence: 99%